Neonatal Sacrococcygeal Teratoma: A Case Report - Riyaz Shrestha; Mohammad Adnan Adil; Swechha Gautam; Prajeet Ray; Rupesh Jung Raut; Dinuj Shrestha; Prayash Chand; Prakash Bista (Journal of Nepal Medical Association)
Sacrococcygeal teratoma is a rare tumour of the coccyx that contains tissues from ectoderm, mesoderm and endoderm. It has a female preponderance with an incidence of 1 in 40,000 live births. Its prognosis depends on the tumour size, weight, APGAR scores, age at presentation, intraoperative injury and malignant potential. We report a case of Sacrococcygeal teratoma in a female neonate of birth weight 3.37 kgs, born to a 34 years primigravi536da. The tumour comprised about 1/3rd of the body weight which created hemodynamic challenges to the new-born. Successful surgical management of the tumour was done with a multidisciplinary team approach.